Penerapan Algoritma Elias Delta Code Untuk Kompresi File Video Pada Aplikasi Video Downloader - Jamiatul Sisca (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2021)
The development of communication media in today's era is very rapid, especially the part of communication media in the form of an application that functions to download a file. one of them is the Video Downloader application which is an application software that functions to download a video file or an audio file. However, there were several problems that were found when the download was finished, especially the download results from the video file. Where, the required video file must have the right resolution and have good quality. However, the problem is the capacity for the required resolution has a large enough capacity for the storage memory that has been provided. Therefore, file compression is required, where this compression must be done using an appropriate algorithm such as using the Elias Delta Code algorithm, where the Elias Delta Code algorithm helps the work process by compressing the size of the video file without reducing the quality of the video. by using Eclipse Juno.